AI-Enhanced Language Design - ChatGPT: Bibliometric Analysis and Potential Uses in the Conservation and Restoration of Tropical Ecosystems - Reyes Palomino, Smith Ervin (2025)
ChatGPT, in line with other established artificial intelligence systems, emerges as an advanced tool based on OpenAI's GPT model. This study focuses on exploring its applicability in the conservation and restoration of tropical ecosystems. A bibliometric analysis dissects the main characteristics, learning systems, and potential applications of ChatGPT. Questioned about its groundbreaking potential in the conservation and restoration of tropical ecosystems, ChatGPT outlines applications in assessment and planning, education, monitoring and rapid response, interaction with field tools, and policy support. Although ChatGPT does not inherently provide scientific support, subsequent analysis confirms that its proposals align with current trends in conservation and restoration. When using tools like ChatGPT in scientific contexts, researchers should adopt a critical approach, verifying the provided responses. Additionally, we underscore the need for further research on the ethics of implementing artificial intelligence in conservation and restoration domains.